Secularism, decolonisation, and the Cold War in South and Southeast Asia - Six, Clemens (Routledge studies in the modern history of Asia, 2018)
The intensifying conflicts between religious communities in contemporary South and Southeast Asia signify the importance of gaining a clearer understanding of how societies have historically organised and mastered their religious diversity. A novel approach to studying secularism in Asia, the book discusses the different ways that global transformations such as decolonisation and the Cold War interacted with local relations to re-shape and re-locate religion in society.